Rear-facing child restraint device performance in side impact crashes - Hauschild, Hans (University of Wisconsin--Whitewater, 2012)
The purpose of this research project was to examine the performance of rear-facing child restraint devices (RFCRD) involved in side impact crashes. Side impact crashes are the second highest crash mode reported by the National Highway Traffic Safety Administration (NHTSA). Child restraint devices (CRDs) are being installed in the center seating position of vehicles because it is thought to be the safest position in the vehicle due to the distance from any intrusion. Children are still being injured in side impact crashes due to the child restraint device moving toward the direction of impact and colliding against the intruding sheetmetal and interior components of a vehicle hit in the side. Testing done by the NHTSA in the Side Impact New Car Assessment Program (SINCAP) in 2007 placed RFCRDs in test vehicles. Subjective analysis of the SINCAP high speed video raised the question examined in this research about the excursions and potential injury of the child occupants in side impacts. The first part of this study examined the maximum head excursion of a 12 month CRABI anthropomorphic test device (ATD) placed in RFCRDs at a change in velocity of 35 km/h (22mph). The change in velocity was determined by using the average of four popular selling small and mid-size vehicles' crash tested by the NHTSA SINCAP program. The purpose of the test series was to determine if a child occupant placed in a CRD in the center seating position would impact the door of a vehicle involved in a higher speed side impact event, such as the NHTSA SINCAP program where a moving deformable barrier traveling at 62 km/h (38.5 mph) impacts the side of a vehicle. After determining the excursion of the ATD head, and determining if the head would hit an intruding door during a side impact event, the ATD and CRD were impacted into a simulated door to determine injury potential at 35 km/h (22 mph) change in velocity. Tests impacting the simulated door were also conducted at 29 km/h (18 mph), and 24 km/h (15 mph) to determine injury potential. In all the sled tests done at 35 km/h (22 mph) the ATD head moved into the crush zone of a sample of smaller and mid-sized vehicles. The potential for severe head injury using all the tested RFCRDs at 35 km/h (22mph) was high when impacting a simulated door. The threshold for lower injury potential was at 24 km/h (15 mph). When the ATD did not impact anything at 35km/h (22 mph) the potential for severe head injury was also low. This study concludes that testing of CRDs needs to be done at higher speeds to better protect children involved in higher speed side impact crashes. Head injury values and excursions both need to be evaluated for reducing injury potential.
This file was last viewed in Adobe Acrobat Pro.
Keywords: Child restraint systems in automobiles; Side--impact collisions